2020
DOI: 10.3390/microorganisms9010049
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation among Stenotrophomonas maltophilia Isolates Has Clinical Relevance: The ANSELM Prospective Multicenter Study

Abstract: The ability to form biofilms is a recognized trait of Stenotrophomonas maltophilia, but the extent of its clinical relevance is still unclear. The present multicenter prospective study (ANSELM) aims at investigating the association between biofilm formation and clinical outcomes of S. maltophilia infections. One hundred and nine isolates were collected from various geographical origins and stratified according to their clinical relevance. Biofilm formation was evaluated by the microtiter plate assay and correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…The ability to form biofilms is one of the most important virulence factors for both pathogens, and the majority of clinical isolates are biofilm producers [ 41 ]. It was shown that S. maltophilia biofilms were up to 128 times more resistant to trimethoprim/sulfamethoxazole and levofloxacin treatment compared with planktonic cells [ 42 ]. Biofilm-mediated antibiotic resistance in clinical A. baumannii strains was also described [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to form biofilms is one of the most important virulence factors for both pathogens, and the majority of clinical isolates are biofilm producers [ 41 ]. It was shown that S. maltophilia biofilms were up to 128 times more resistant to trimethoprim/sulfamethoxazole and levofloxacin treatment compared with planktonic cells [ 42 ]. Biofilm-mediated antibiotic resistance in clinical A. baumannii strains was also described [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that more than 60% of infections are associated with the ability of a microorganism to form a biofilm, much attention is also paid to research on the anti-biofilm properties of ceragenins. Biofilm is also an important factor in S. maltophilia infections, [48] and the anti-biofilm effects of ceragenins suggest that they have the potential for application against S. maltophilia strains [19,49]. The high anti-biofilm activity of ceragenins is confirmed by many previous studies [50][51][52].…”
Section: Discussionmentioning
confidence: 53%
“…S. maltophilia can adhere to several surfaces and grow as a biofilm, a microbial consortium embedded in a self-produced polymeric matrix and inherently resistant to antibiotic therapy and the host immune response [ 6 ]. Several studies have recently indicated that the ability to form biofilm is highly conserved in clinically relevant S. maltophilia isolates [ 7 ]. Biofilm formation can occur on inert surfaces (e.g., respiratory tubes and nebulizers, intravenous cannulae, prosthetic devices, and dental unit waterlines), causing medical implant-associated infections [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The genetic regulation of biofilm formation in S. maltophilia is complex, as suggested by the significant number of genes involved [ 6 ]. Several studies indicated that the ability of S. maltophilia to form biofilm is mainly influenced by bacterial virulence factors (e.g., flagella, pili, LPS/exopolysaccharide biosynthesis, motility) [ 7 ], cell surface traits (e.g., outer membrane proteins, hydrophobicity) [ 9 , 10 ], and quorum-sensing communication [ 11 ].…”
Section: Introductionmentioning
confidence: 99%